Multivariate analysis of preoperative and postoperative neutrophil-to-lymphocyte ratio as an indicator of head and neck squamous cell carcinoma outcome. Issue 8 (August 2018) - Muhaxheri, G.; Vucicevic Boras, V.; Fucic, A.; Plavec, D.; Sekerija, M.; Filipovic, M.; Grsic, K.; Stubljar, B.; Krnic, T.; Vrdoljak, B.
Abstract: Recent publications have highlighted a greater utility of routine blood tests in patients with various cancers than previously assumed. It appears that the neutrophil-to-lymphocyte ratio (NLR) may be a good predictive biomarker for overall survival (OS) and disease-free survival (DFS). Preoperative and postoperative NLR data for patients with head and neck cancers have yet to be established. The aim of this study was to evaluate the preoperative and postoperative NLR in 182 patients with head and neck squamous cell carcinoma and to determine the association of NLR with OS and DFS. The statistical analysis of OS and DFS and their predictors was performed using Kaplan–Meier survival analysis and multivariate Cox proportional hazards regression analysis, with factors including age, sex, alcohol and tobacco use, tumour location, treatment after surgery, and lymphocyte and neutrophil counts. Longer OS was significantly associated with not consuming alcohol, preoperative neutrophil and lymphocyte counts, preoperative NLR, and the difference between the preoperative and postoperative NLR ( P  = 0.016). Longer DFS was significantly associated with not consuming alcohol, preoperative neutrophil and lymphocyte counts, postoperative NLR, and the difference between preoperative and postoperative NLR ( P  = 0.028).